The Effect of Cultivation Method of Strawberry (Fragaria x ananassa Duch.) cv. Honeoye on Structure and Degradation Dynamics of Pectin during Cold Storage - Drobek, Magdalena (Molecules, 2020)
The high quality and long shelf life of strawberry fruit are largely dependent on the cultivation method. The goal of this experiment was to study the effect of different cultivation methods on molecular structure and rheological properties of pectin extracted from strawberry quality parameters during cold storage. Three methods of cultivation of strawberry cv. Honeoye were tested: organic cultivation on raised beds, organic cultivation with the flat-planted method and conventional cultivation with the flat-planted method. The nanostructure of pectin (AFM), its chemical structure (FT-IR) and rheological properties were studied. The fruits were also tested by size, dry matter, firmness, acidity and the content of soluble solids, anthocyanin, phenolics, vitamin C and galacturonic acid. Pectin isolated from organic strawberries was more rapidly degraded than conventional strawberry pectin, which limits the possibilities for their processing and use as gelling or stabilizing agents at 20 °C. The differences in fruit quality were particularly noticeable with respect to the anthocyanin content, which was significantly higher for organic strawberry. The organic fruit also had better sensory properties because of its lower acidity and higher soluble solid content (SSC). These and other results from this experiment showed that strawberries produced by organic farming methods had better biochemical properties compared to conventional fruit; however, pectin transformation undergone faster limits their further technological applications.